DESIGNING A MULTICULTURAL HYBRID LEARNING FRAMEWORK FOR SOCIAL STUDIES EDUCATION IN A DIVERSE INDONESIAN CLASSROOM - Ali Al-Jubouri; Wahju Dyah Laksmi Wardhani; Tasnia Islam Islam; Cipto Duwi Priyono (Yayasan Adra Karima Hubbi, 2025)
The diversity in Indonesian classrooms presents both opportunities and challenges for social studies education. The evolving cultural and ethnic backgrounds of students necessitate the development of an inclusive and adaptable educational framework. This study explores the design of a multicultural hybrid learning framework tailored for social studies education in Indonesia. The primary objective of the research is to develop an effective, culturally responsive teaching model that integrates both traditional and digital learning methods to cater to diverse student needs. A mixed-methods approach was employed, combining qualitative interviews with social studies educators and quantitative surveys of students across different regions. The research findings indicate that the proposed hybrid framework fosters a more engaging and equitable learning environment by incorporating culturally relevant content, interactive digital tools, and collaborative learning strategies. Furthermore, the study highlights the importance of teacher training in multicultural competence and the integration of technology in enhancing students' critical thinking and social awareness. The study concludes that a hybrid learning model, when thoughtfully implemented, can significantly improve the inclusivity and effectiveness of social studies education in a multicultural context. This research contributes to the broader field of education by offering a model for adapting social studies teaching in diverse classrooms.